A CLINICAL EVALUATION OF ANTISTRESS ACTIVITY OF ASHWAGANDHA (WITHANIA SOMNIFERA DUNAL) ON EMPLOYEES EXPERIENCING MENTAL STRESS AT WORK PLACE - Amit Ashok, Gajarmal; M.B., Shende (International Journal of Ayurveda and Pharma Research, 2015)
According to various surveys, the stress is the major problem for many diseases ranging from psychiatric disorders to endocrine disorders. In national capital regions like Mumbai, Chennai, Kolkata and Pune. As per the survey over 76% of senior and middle level executives working endure the highest levels of stress resulting into mental and physical fatigue. Pertaining to the stress, modern medicine can provide some curable results but they are complicated and unsatisfactory. So the answer is hidden in Ayurveda i.e. Rasayana Chikitsa (Rejuvenation therapy). As similar to the modern concept of adaptogenic agents which gives the protection to the human physiological system against diverse stressor, recent studies shows that the Rasayana Dravyas having adaptogens which could induce a state of non-specific increase of resistance to affect internal homeostasis. The adaptogens improve the response to stress and help the body to adapt by normal physiological processes in times of increased stress. Therefore, Ashwagandha which is the best in Rasayana Karma, identified as Withania somnifera Dunal, is selected for the study. The present research work has been undertaken with the main objective as the clinical evaluation of antistress effect of Ashwagandha (Withania somnifera Dunal) on employees at different work places by various scientific parameters.